2004
DOI: 10.1161/01.cir.0000133324.38115.0a
|View full text |Cite
|
Sign up to set email alerts
|

Local Gene Transfer of phVEGF-2 Plasmid by Gene-Eluting Stents

Abstract: Background— Drug-eluting stents represent a useful strategy for the prevention of restenosis using various antiproliferative drugs. These strategies share the liability of impairing endothelial recovery, thereby altering the natural biology of the vessel wall and increasing the associated risk of stent thrombosis. Accordingly, we tested the hypothesis that local delivery via gene-eluting stent of naked plasmid DNA encoding for human vascular endothelial growth factor (VEGF)-2 could ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(74 citation statements)
references
References 58 publications
0
72
1
1
Order By: Relevance
“…6,[8][9][10][11][12][13][14] This past work has focused largely on the encapsulation of plasmid DNA in thin films of degradable polymer 8, 10-13 or the tethering of viruses to collagen-coated stents 9 or bare metal stents. 14 In the long term, methods for non-viral gene delivery have the potential to be safer than methods based on the use of viruses.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10][11][12][13][14] This past work has focused largely on the encapsulation of plasmid DNA in thin films of degradable polymer 8, 10-13 or the tethering of viruses to collagen-coated stents 9 or bare metal stents. 14 In the long term, methods for non-viral gene delivery have the potential to be safer than methods based on the use of viruses.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Losordo et al were able to deliver a vascular endothelial growth factor (VEGF)-2 plasmid in a vascular stent. They found that the treatment group had an improved completeness of endothelialization, improved luminal cross-sectional area and vessel function as measured by nitric oxide production in hypercholesterolemic rabbits [111]. This approach shows much promise as a delivery system, but single gene therapy may not yield straightforward results.…”
Section: Gene Transfer Strategies To Promote An Endothelial Monolayermentioning
confidence: 99%
“…27 Capitalizing on the advent of stent technology capable of drug delivery, we have recently shown that gene-eluting stents coated with phVEGF-2 naked plasmid DNA accelerate reendothelialization and inhibit neointimal proliferation in a hypercholesterolemic rabbit iliac angioplasty model. 28 In the present issue of Circulation, Hedman et al 1 report the provocative results of a phase II, randomized, placebocontrolled, double-blind study designed to test the feasibility, tolerability, and efficacy of VEGF gene therapy to prevent restenosis after coronary stenting. Thus, another step toward ameliorating, rather than perturbing, the biology of the artery wall as a restenosis prevention strategy has been taken.…”
Section: See P 2677mentioning
confidence: 99%